2000
DOI: 10.1002/1096-8628(20001218)95:5<454::aid-ajmg9>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of uniparental disomy to congenital development defects in children born to mothers at advanced childbearing age

Abstract: Most instances of maternal uniparental disomy (UPD) start as trisomies and, similar to the latter, show a significant increase of mean maternal age at delivery. To investigate the incidence of UPD in offspring of older mothers, we investigated two groups of patients: 1) 50 patients with unclassified developmental defects born to mothers 35 years or older at delivery were tested for UPD for all autosomes by means of microsatellite marker analysis; 2) The incidence of UPD versus other etiologies in correlation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…Another possible factor related to unfavorable impact is fetal uniparental disomy (UPD). In fact, contribution of maternal UPD for chromosome 7 to growth retardation in the prenatal and postnatal period is known as one of the genetic causes of Silver–Russell syndrome . In our case, UPD testing on genomic DNA was not available as the parents declined it.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Another possible factor related to unfavorable impact is fetal uniparental disomy (UPD). In fact, contribution of maternal UPD for chromosome 7 to growth retardation in the prenatal and postnatal period is known as one of the genetic causes of Silver–Russell syndrome . In our case, UPD testing on genomic DNA was not available as the parents declined it.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, contribution of maternal UPD for chromosome 7 to growth retardation in the prenatal and postnatal period is known as one of the genetic causes of Silver-Russell syndrome. 6 In our case, UPD testing on genomic DNA was not available as the parents declined it. However, UPD itself, even if our case had it, may have little impact on the occurrence of observed abnormality in the pregnancy, because previous UPD molecular studies have shown that FGR in CPM2 occurs, regardless of the presence of UPD.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, mechanisms mediating the effect of advancing maternal age on ASD risk have not been frequently investigated. Advancing maternal age has been associated with chromosomal changes 32, 33 and genomic modifications. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Lindor et al investigated 25 cases with a broad spectrum of multiple congenital anomalies, short stature, mental retardation, and various dysmorphic features [27]. Ginsburg et al [28] found one case with maternal UPD 14, one with paternal UPD 15, and one with maternal UPD 16 associated with a 46,XY/46,XY,der(1)(1;16) karyotype [29] in a group of 45 children with various congenital defects born to mothers older than 35 years. In both studies IUGR or primordial growth retardation was not an obligatory feature.…”
Section: Discussionmentioning
confidence: 99%